ANALYSIS OF ENTREPRENEURIAL COMPETENCE ON BUSINESS PERFORMANCE IN MSMES KAHUT SIGERBORI ECOPRINT BANDAR LAMPUNG - Anita Najla Dhia; Iskandar Ali Alam (ZILLZELL MEDIA PRIMA, 2024)
The purpose of this paper is to assess entrepreneurial competence and business performance in micro, small and medium enterprises (MSMEs) Kahut Sigerbori Ecoprint in Bandar Lampung, as well as to test the impact of entrepreneurial competence on business performance. This writing uses qualitative writing design, uses a descriptive approach and uses observation and interview methodologies. This writing uses data processing methodologies such as data collection, data reduction, data presentation, and conclusions. The writing population is 9 workers and 1 owner of Kahut Sigerbori Ecoprint Bandar Lampung. An interview was conducted with one of the individuals who served as the owner of an MSME. Research findings show that entrepreneurial competence plays an important role in managing and improving company performance in MSMEs Kahut Sigerbori Ecoprint. The business performance of MSMEs Kahut Sigerbori Ecoprint has shown remarkable progress, with significant and substantial revenue growth. There is a direct correlation between entrepreneurial ability and business performance. MSMEs Kahut Sigerbori MSMEs Ecoprint.